Strength and VO2max Changes by Exercise Training According to Maturation State in Children - Liliana Aracely Enríquez-; Andrea Ornelas-López; Lidia G. De León; Natanael Cervantes-Hernández; Estefanía Quintana-Mendias; Luis Alberto Flores (MDPI AG, 2022)
The health benefits of physical activity (PA) are widely recognized; however, biological maturation contributions are a subject that has been little studied, which is why the aim of this study was to analyze the effect of a six-week training program at moderate-intensity on the muscular strength and aerobic capacity in children between nine and 13 years (13 ± 1.0 years) according to their maturation state. Twenty-six schoolchildren (15 girls) participated in a six-week physical exercise program based on aerobic/anaerobic capacity and coordination skills. Maximal oxygen uptake (VO2max), trunk-lift, push-ups, curl-ups, and handgrip strength (both hands) were measured as response variables. Body mass index (BMI), skeletal maturity indicator (SMI), peak height velocity (PHV), age on peak height velocity (APHV) and sex were considered as covariates. The results of VO2max, push-ups, curl-ups, and handgrip strength were higher after the exercise program in the whole group (p < 0.05). The VO2max showed a greater increase in the normal-weight than in the overweight-obesity children (p = 0.001). Higher results in dominant handgrip strength were observed in girls (p = 0.003). The PHV before intervention presented a positive correlation with the dominant handgrip strength in all kids (r = 0.70, p = 0.001). As a conclusion, the six-week training program improved the physical fitness of children independent of the maturation state. Somatic maturation increases the physical abilities in schoolchildren.